Influenza virus-related critical illness: pathophysiology and epidemiology - Kalil, Andre C.; Thomas, Paul G. (Critical care (London, England), 2019)
Influenza virus affects the respiratory tract by direct viral infection or by damage from the immune system response. In humans, the respiratory epithelium is the only site where the hemagglutinin (HA) molecule is effectively cleaved, generating infectious virus particles. Virus transmission occurs through a susceptible individual’s contact with aerosols or respiratory fomites from an infected individual. The inability of the lung to perform its primary function of gas exchange can result from multiple mechanisms, including obstruction of the airways, loss of alveolar structure, loss of lung epithelial integrity from direct epithelial cell killing, and degradation of the critical extracellular matrix. Approximately 30–40% of hospitalized patients with laboratory-confirmed influenza are diagnosed with acute pneumonia. These patients who develop pneumonia are more likely to be < 5 years old, > 65 years old, Caucasian, and nursing home residents; have chronic lung or heart disease and history of smoking, and are immunocompromised. Influenza can primarily cause severe pneumonia, but it can also present in conjunction with or be followed by a secondary bacterial infection, most commonly by Staphylococcus aureus and Streptococcus pneumoniae . Influenza is associated with a high predisposition to bacterial sepsis and ARDS. Viral infections presenting concurrently with bacterial pneumonia are now known to occur with a frequency of 30–50% in both adult and pediatric populations. The H3N2 subtype has been associated with unprecedented high levels of intensive care unit (ICU) admission. Influenza A is the predominant viral etiology of acute respiratory distress syndrome (ARDS) in adults. Risk factors independently associated with ARDS are age between 36 and 55 years old, pregnancy, and obesity, while protective factors are female sex, influenza vaccination, and infections with Influenza A (H3N2) or Influenza B viruses. In the ICU, particularly during the winter season, influenza should be suspected not only in patients with typical symptoms and epidemiology, but also in patients with severe pneumonia, ARDS, sepsis with or without bacterial co-infection, as well as in patients with encephalitis, myocarditis, and rhabdomyolysis.